A clustering method for analysis of morphology of short natural fibers in composites based on X-ray microtomography. (November 2017) - Madra, Anna; Adrien, Jérôme; Breitkopf, Piotr; Maire, Eric; Trochu, François
Abstract: The work presented here concerns the methodology for the analysis of X-ray micro-CT scans of composite materials with a discontinuous phase. An automatized method has been devised for the measurement of geometric features and identification of distinct morphological types. This approach offers new insights into the composition of a microstructure based on the analysis of phase morphology and its relative volume percentage. It stays in contrast to the frequency-based approach that attributes the same importance to all elements of the structure, and is thus biased towards numerous, but not necessarily essential components of the material. The method is general and can be applied to any type of discontinuous, dispersed phase in composites identified with X-ray micro-tomography. We have verified our approach for short natural fibers but it may be of interest for characterizing void distribution in RTM manufactured composites or cracks after failure.